The genesis of forensic research of documents as the branch of forensic technology (Law and Safety, 2020)
The history of the falsification of various documents for illegal purposes accompanies the entire history of human civilization, so the study of the evolution of methods of documenting information and related methods of forgery is one of the methods of improving forensic knowledge. The examination of documents similarly has a long history and is directly related to the emergence and spread of writing.At the present stage of development of forensic document research, the achievements of various sciences are actively used to reveal the patterns in the field of forensic technology and its improvement. In particular, the study of the anatomical characteristics of writing and motor skills during the analysis of certain elements of handwriting; physiological processes that form the basis of movement control and reproduce written features or their combinations. The coordination of movements in the distribution of manuscripts according to the pace of writing is separately studied. Factors influencing the formation of written speech are determined by conducting experiments. Internal and external factors are taken into account, which allow to reconstruct the psycho-physiological features of the person who wrote the document, without which the establishment of its authorship is extremely problematic. Data of physiology and psychology help in the process of substantiating the stability of handwriting elements, drawing parallels between psycho-physiological characteristics of a person and certain graphic features.Considering the acquired historical experience, modern forensic research can be divided into three categories: 1) handwriting, where the main purpose is to establish the executor of the document; 2) auto-research – finding out the authorship of the text of the document; 3) technical and forensic, which allow to accurately establish the remaining components of the document.Forensic examination of documents has passed a long way in historical evolution. In its modern form, it was developed in the second half of the XX century due to a combination of theoretical principles and special methods borrowed from the natural and technical sciences. It allowed to determine as accurately as possible the technical features of producing a document or its part thereof, identifying the used tools and materials.
Keywords: a document; document authenticity; document examination; an offense; document research